Iodine prophylaxis in pregnant women in Poland - where we are? (update 2015). Issue 1 (December 2015) - Zygmunt, Arkadiusz; Lewinski, Andrzej
Abstract Introduction of the model of iodine prophylaxis based on the consumption of iodized salt in 1997 has eliminated the iodine deficiency in Poland. However, in accordance with the current recommendations, all women who are planning to be pregnant or are pregnant or breastfeeding should receive an additional dose of iodine at 150–200 mcg / day because of the increased body's need for iodine during this period. Studies show that only part of women in Poland conduct a proper iodine prophylaxis and it is often initiated in the second and third trimester of pregnancy. The authors try to analyze the possible causes of this situation, pointing out what could be done to increase the degree of compliance with iodine prophylaxis during pregnancy and physiological lactation in Poland.